To Quote or Not to Quote: Literary Quotations as Change from Above - Chapman, Don (Studia Anglica Posnaniensia, 2019)
Phrases deriving from literary quotations are sometimes included in language histories as contributions from famous writers, like Shakespeare. This paper will argue that the label “change from above” is still a useful label for the addition of literary phrases to the language, even if such an addition is not typical of the variationist changes for which the label was coined. This paper will also demonstrate that the process of incorporating a literary quotation into the language involves several alterations to the quotation’s form and meaning, and that these changes are also part of the “change from above” characterizing the adoption of literary phrases.